Mirror-mirror on the wall, what climate change adaptation strategies are practiced by the Asian's fishermen of all? - Mohamed Shaffril, Hayrol Azril; Abu Samah, Asnarulkhadi; Samsuddin, Samsul Farid; Ali, Zuraina (Elsevier, 2019)
This systematic review article focuses on the adaptation strategies of Asian fishermen toward climate change impacts. Generally, the fact that climate change is not a new phenomenon has attracted scholars to conduct numerous relevant studies. Unfortunately, most past researches were not from the perspectives of social science of the Asian's community. Hence, the present study reviewed a considerable amount of past studies on the act of adjusting with environmental change among the Asian fishermen which is known as one of the communities that are highly dependent on nature stability. Meanwhile, Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) was adopted for the review of the current research which utilised two main journal databases, namely Scopus and Web of Science. Accordingly, the searching efforts resulted in a total of 18 articles that can be analysed systematically. Most importantly, the review managed to formulate five main themes, namely livelihood diversification, social, physical infrastructure, awareness-knowledge-experience, and conservation and enforcement based on the thematic analyses. Overall, further analysis of the five themes resulted in the establishment of a total of 21 sub-themes. Finally, a number of recommendations were presented at the end of this research for the reference of future scholars.